Effects of Fluorosis and Bleaching on Shear Bond Strengths of Orthodontic Brackets - Adanir, Necdet; Türkkahraman, Hakan; Güngör, Ahmet Yalçın (European Journal of Dentistry, 2007)
Objectives: To evaluate the effects of fluorosis and bleaching on shear bond strengths of orthodontic brackets.Methods: A total of 45 (30 fluorosed and 15 non-fluorosed) non-carious freshly extracted human permanent premolar teeth which were extracted for orthodontic reasons and without any caries or visible defects were used in this study. Fluorosed teeth were selected according to the modified Thylstrup and Fejerskov index (TFI), which is based on the clinical changes in fluorosed teeth. First group consisted of 15 fluorosed teeth. Second group of fluorosed teeth were bleached with a 35% hydrogen peroxide office bleaching agent. Third group served as control. No bleaching procedure was applied. Orthodontic brackets were bonded with a light cure composite resin and cured with a halogen light. After bonding, shear bond strengths of the brackets were tested with Universal testing machine.Results: The results showed that fluorosis only and bleaching of fluorosed teeth significantly reduced the bond strengths of the orthodontic brackets (P>.001). Although bleaching of fluorosed teeth decreased the values more, no statistically significant difference was found between fluorosis group and fluorosis+bleaching group (P<.05).Conclusions: Fluorosis and bleaching of fluorosed teeth reduce bracket bond strength to enamel, but the bond strength with these still exceed the minimum 6 to 8 MPa required to expect adequate clinical performance. (Eur J Dent 2007;1:230-235)
Keywords: Fluorosis; Bleaching; Shear bond strength; Hydrogen peroxide